(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The paper The Reality of East Germany reflected in the German lexis. Is “Ostalgie” still present in today’s German? based on the master’s thesis German Lexis of the GDR period mirrored in the „Duden” dictionary deals with lexis classified in the Duden dictionary as characteristic of the GDR period. Diachronic and synchronic analysis of the excerpted units in terms of their parts of speech, semantics, etymology and usefulness are preceded by a theoretical background, which tries to define the status of the German language after the World War II and in the GDR. The main aim of the paper was to demonstrate to what extent the reality in the Eastern Germany shaped German in the GDR and subsequently in Germany after its reunification.